Lnc-EST885 promotes hepatocellular carcinoma metastasis through PI3K / AKT pathway by interaction with TRAF4 - Shaoliang Zhu; Gang Wang; Yuxuan Zhang; Mengjie Zou; Zhi Li; Shenhong Qu; Xiaosu Zou; Wenqian Nong; Weiwei Miao; Qicong Chen; Juanmei Mo; Huibing Chen; et al. (Translational Oncology)
Background: Hepatocellular carcinoma (HCC) represents a major malignancy globally, characterized by high malignancy and intricate molecular mechanisms. This study aims to explore the role of the long non-coding RNA (lncRNA) lnc-EST885 in HCC development. Methods: Cell experiments including FISH, western blot, flow cytometry and functional analysis were used to elucidate the effects of lnc-EST885 on cell proliferation, apoptosis, migration and EMT processes. RNA pull-down and ESI-FT-ICR-MS were used to identify proteins that interact with lnc-EST885 and were verified by RIP-qPCR. Furthermore, the association of lnc-EST885 and TRAF4 with HCC prognosis and metastasis was evaluated through bioinformatics analysis and animal models. Results: lnc-EST885 is one of the lncRNAs with the highest expression levels in M2-type macrophages. The expression of lnc-EST885 in HCC tissues is significantly higher than in normal tissues, and high expression is associated with poor prognosis. Functional experiments have shown that lnc-EST885 significantly promotes the proliferation and migration of liver cancer cells, inhibits apoptosis, and induces EMT. Studies in a mouse lung metastasis model have also confirmed that lnc-EST885 promotes the pulmonary metastasis of HCC cells in vivo. Mechanistic studies have revealed that lnc-EST885 can bind to the TRAF4 protein, activating the PI3K/AKT signaling pathway, thereby promoting the proliferation, migration, and EMT capability of liver cancer cells, contributing to the malignant phenotype of HCC. Conclusion: lnc-EST885 plays a crucial role in the development of liver cancer, serving as a potential biomarker for predicting HCC prognosis and providing a new target for HCC treatment.